ANALISIS RESEPSI KHALAYAK TERHADAP MAKNA BODY POSITIVITY PADA VIDEO KLIP “TUTUR BATIN” KARYA YURA YUNITA - Achsani, Valida; Wibowo, Arif (Communications, 2023)
This study aims to find out how the audience receives the message of body positivity through the video clip "Tutur Batin" by Yura Yunita. From the results, the researchers positions the informants into three categories according to Stuart Hall, namely dominant hegemonic position, negotiated position and oppositional position. This type of research is descriptive qualitative research. Researchers conducted in-depth interviews with ten informants consisting of six women and four men with an age range of around 13-38 years. Through interviews that have been conducted, researchers get various results, this is influenced by differences in the background of each informant. From the analysis that has been carried out, the results show that of the ten informants studied, six informants are in the dominant hegemonic category, while the other four are in negotiated positions and no informants are found in oppositional positions, so there are only two categories obtained.